2017
DOI: 10.1590/2317-1545v39n2167788
|View full text |Cite
|
Sign up to set email alerts
|

Changes in desiccation tolerance and respiratory rates of immature Caesalpinia echinata Lam. Seeds

Abstract: -Seed storage is an important tool for ex situ conservation. Orthodox seeds can be stored for long periods, but recalcitrant seeds generally only for short periods. There is wide variation in the degree of desiccation tolerance between orthodox and recalcitrant seeds, leading authors to suggest levels of recalcitrance and, more recently, that there are variations in the stage of maturity at seed dispersal. Thus, recalcitrant behavior would be a result of premature dispersal from the mother plant. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
2
3
0
2
Order By: Relevance
“…Thus, one cannot consider storing I. vera embryos merely by lowering the temperature and expecting metabolism to stop: they will continue to respire. As shown in previous studies (Araujo and Barbedo, 2017;Bonjovani and Barbedo, 2019;Guardia et al, 2020), there were no patterns of change in respiration with reduction of water content for most embryos from different regions. This result differs from the outcomes for desiccation-tolerant seeds in general, or even for some desiccation-sensitive seeds, such as Castanea sativa (Leprince et al, 1999) and Eugenia pyriformis (Lamarca et al, 2020).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, one cannot consider storing I. vera embryos merely by lowering the temperature and expecting metabolism to stop: they will continue to respire. As shown in previous studies (Araujo and Barbedo, 2017;Bonjovani and Barbedo, 2019;Guardia et al, 2020), there were no patterns of change in respiration with reduction of water content for most embryos from different regions. This result differs from the outcomes for desiccation-tolerant seeds in general, or even for some desiccation-sensitive seeds, such as Castanea sativa (Leprince et al, 1999) and Eugenia pyriformis (Lamarca et al, 2020).…”
Section: Resultssupporting
confidence: 66%
“…The results of the initial characterization showed that, although all the fruits had been collected when they were ripe, their embryos showed maturation differences: those of RIB, for example, were closer to physiological maturity than the others, because: a) although the embryos from all regions had very high water content, above 50%, typical for species of the genus Inga (Mata et al, 2013;Schulz et al, 2014), those from RIB had the lowest water potential. This result indicates more binding sites, therefore a better structured matrix (Vertucci and Farrant, 1995); b) the embryos accumulated more dry weight (Marcos-Filho, 2015); c) they had a lower respiration rate, indicating that they were among more mature embryos (the more mature, the lower the respiratory rate, Araujo and Barbedo, 2017) and embryos that had already started germination (the more advanced in germination, the higher the respiratory rates, Hell et al, 2019); d) they had the longest mean germination time, indicating that they had not started germination before harvest, which is relatively common for embryos of this species (Andreo et al, 2006;Bonjovani and Barbedo, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…There are higher respiratory values for the 2011 embryos in comparing their rates with those of 2010 (Figures 1 and 3). Seed respiration rates are usually lower in the final stages of maturation, as verified in legume seeds such as soybean (Miller et al, 1983), brazilwood (Araujo & Barbedo, 2017), and ironwood (Bragante et al, 2018). Therefore, it is probable that the embryos of 2011 with higher rates of respiration were at a maturation stage prior to 2010.…”
Section: /10mentioning
confidence: 99%
“…This was also verified for seeds from other Leguminosae species, such as Caesalpinia echinata Lam. (Araujo & Barbedo, 2017;Lamarca & Barbedo, 2012) and Libidibia ferrea (Mart. exTul.)…”
Section: Fungicidal Treatment and Respiration At Different Storage Tementioning
confidence: 99%
“…A deterioração é um processo complexo e progressivo que envolve mudanças de natureza metabólica, bioquímica, citológica, genética e fisiológica. A atividade metabólica é acelerada principalmente quando o teor de água das sementes é alto e as temperaturas ambientais também, elevando as taxas respiratórias, e consequentemente, o consumo das reservas (CARVALHO & NAKAGAWA, 2012;BARBEDO et al, 2013;CACCERE et al, 2013;MARCOS-FILHO, 2015;ARAÚJO & BARBEDO, 2017). Altos teores de água favorecem o desenvolvimento de microrganismos, pondedo também, acelerar o processo de deterioração (CARVALHO & NAKAGAWA, 2012;MARCOS-FILHO, 2015;FRANÇOSO & BARBEDO, 2016;PARISI et al, 2016).…”
Section: Longevidade E Viabilidade De Sementesunclassified